1992
DOI: 10.1002/jbm.820260308
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of photoreactive poly(ethylene glycol) and its application to the prevention of surface‐induced platelet activation

Abstract: Photoreactive poly(ethylene glycol) (PEG) was synthesized by reacting 4-fluoro-3-nitrophenyl azide (FNPA) with sodium salt of PEG. The synthesized 4-azido-2-nitrophenyl PEG (ANP-PEG) was characterized by 1H-NMR, IR, and UV spectroscopy. ANP-PEG was grafted to dimethyldichlorosilane-coated glass (DDS-glass) by photolysis without any premodification of the surface. The effects of various grafting factors, such as the polymer adsorption time, concentration of ANP-PEG, and UV irradiation time, on the PEG grafting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…(ethylene glycol) 27 and heparin. 28 polyethylene 5.7 min, polypropylene 7.3 min, polyureAryl azides containing phosphorylcholine endthane 8.0 min, and polyvinylchloride-T 9.9 min.…”
Section: Surface Analysisunclassified
“…(ethylene glycol) 27 and heparin. 28 polyethylene 5.7 min, polypropylene 7.3 min, polyureAryl azides containing phosphorylcholine endthane 8.0 min, and polyvinylchloride-T 9.9 min.…”
Section: Surface Analysisunclassified
“…[14][15][16][17] Numerous investigators have found that foreign surfaces rapidly adsorb plasma proteins when exposed to blood, 18 so it is essential to have an understanding of protein-polymer interaction for the development of antithrombogenic material. Hydrogel grafted surfaces by ␥-irradiation method and the protein interaction and morphology of platelets onto the surfaces have been studied by Sharma et al 19,20 Thermoplastic elastomers are triblock copolymers, the central portion being elastomeric with short, glassy blocks on either side.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 On the contrary, highly hydrophilic molecules, such as 2-hydroxymethylmethacrylate and polyethyleneglycol, have been grafted onto surfaces in order to inhibit cell adhesion. 3,4 However, these surfaces are monofunctional and irresponsive to stimuli.…”
Section: Introductionmentioning
confidence: 99%